Semiotyka twarzy kata i ofiary - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Murderous ideologies drive and fabricate innumerable forms of social falsehood. One of the objects of the perfidious falsification of reality generated in the totalitarian system is the human face. Drawing on classics of Polish and world cinema, and also on the memory of culture, Marek Hendrykowskis study contains a semiotic analysis of the deep structures of images, which present the executioner-victim based on violence executioner as a variant of inter-human relations in totalitarian systems.